Coherent J/ψ photoproduction in ultra-peripheral Pb-Pb collisions at √ˢɴɴ =2.76TeV - Abelev, B.; Adam, J.; Adamovã, D.; Adare, A.M.; Aggarwal, M.M.; Aglieri Rinella, G.A.; Agnello, M.; Agócs, A.G.; Agostinelli, A.; Aguilar Salazar, S.; Ahammed, Z.; Ahmad Masoodi, A.; et al. (Elsevier, 2013)
The first measurement of J/ψ photoproduction in ultra-peripheral Pb–Pb collisions at a center-of-mass energy √ˢɴɴ = 2.76 TeV has been carried out with the ALICE experiment at the LHC. The J/ψ meson is identified via its dimuon decay in the forward rapidity region using the muon spectrometer. The analysis is based on an event sample corresponding to an integrated luminosity of about 55 μb⁻¹. The cross section for coherent J/ψ production in the rapidity interval −3.6 < y < −2.6 is measured to be dσᶜᵒʰᴊ/ψ/ dy = 1.00 ± 0.18(stat)⁺⁰·²⁴₋₀.₂₆(syst) mb. The result is compared to theoretical models and is found to be in good agreement with those incorporating nuclear gluon shadowing.
Keywords: J/ψ photoproduction; Ultra-peripheral Pb–Pb collisions; https://purl.org/pe-repo/ocde/ford#1.03.03